Economics of Internet Advertising - Langmajerová, Lucie; Janíčko, Martin, 1983-; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
The goal of this thesis is to answer the question what are the main drivers of the click probability as well as evaluate price efficiency of banner dimensions. Moreover, this work should help media planners to better optimize campaigns from the perspective of both costs and generated clicks. The main econometric methods used are logistic regression and decision tree. Furthermore, to involve price metric, score cards are applied. The key finding is that larger banners are more likely to be clicked on however just for desktops and laptops. Moreover, interactive banners have a higher probability of click as well as web page specific banner placement which is closely associated with banner targeting. On the contrary, the claim that likelihood of click in the campaign decreases over time was not accepted. Finally, price metric shows high efficiency of videos as well as images. Seznam.cz was found the most effective medium thanks to weather targeting.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses